Effect of norepinephrine on spinal cord blood flow and parenchymal hemorrhage size in acute-phase experimental spinal cord injury - Soubeyrand, Marc (Springer Berlin Heidelberg, 2013)
PURPOSE: In the acute phase of spinal cord injury (SCI), ischemia and parenchymal hemorrhage are believed to worsen the primary lesions induced by mechanical trauma. To minimize ischemia, keeping the mean arterial blood pressure above 85 mmHg for at least 1 week is recommended, and norepinephrine is frequently administered to achieve this goal. However, no experimental study has assessed the effect of norepinephrine on spinal cord blood flow (SCBF) and parenchymal hemorrhage size. We have assessed the effect of norepinephrine on SCBF and parenchymal hemorrhage size within the first hour after experimental SCI. METHODS: A total of 38 animals were included in four groups according to whether SCI was induced and norepinephrine injected. SCI was induced at level Th10 by dropping a 10-g weight from a height of 10 cm. Each experiment lasted 60 min. Norepinephrine was started 15 min after the trauma. SCBF was measured in the ischemic penumbra zone surrounding the trauma epicenter using contrast-enhanced ultrasonography. Hemorrhage size was measured repeatedly on parasagittal B-mode ultrasonography slices. RESULTS: SCI was associated with significant decreases in SCBF (P = 0.0002). Norepinephrine infusion did not significantly modify SCBF. Parenchymal hemorrhage size was significantly greater in the animals given norepinephrine (P = 0.0002). CONCLUSION: In the rat, after a severe SCI at the Th10 level, injection of norepinephrine 15 min after SCI does not modify SCBF and increases the size of the parenchymal hemorrhage.